2013
DOI: 10.1001/jamainternmed.2013.10797
|View full text |Cite|
|
Sign up to set email alerts
|

The Quality of Supportive Cancer Care in the Veterans Affairs Health System and Targets for Improvement

Abstract: IMPORTANCE Characterizing the quality of supportive cancer care can guide quality improvement. OBJECTIVE To evaluate nonhospice supportive cancer care comprehensively in a national sample of veterans. DESIGN, SETTING, AND PARTICIPANTS Using a retrospective cohort study design, we measured evidence-based cancer care processes using previously validated indicators of care quality in patients with advanced cancer, addressing pain, nonpain symptoms, and information and care planning among 719 veterans with a 2008 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 45 publications
1
50
0
Order By: Relevance
“…Quality metrics for palliative care have also been developed and implemented in the Veterans Health Administration, but require manual chart abstraction and may be challenging to scale to other healthcare systems. 19 In the search for feasible, reliable, and valid palliative care quality metrics, automated methods of using the electronic health record (EHR) are an attractive option. However, the EHR has often not delivered on its potential.…”
mentioning
confidence: 99%
“…Quality metrics for palliative care have also been developed and implemented in the Veterans Health Administration, but require manual chart abstraction and may be challenging to scale to other healthcare systems. 19 In the search for feasible, reliable, and valid palliative care quality metrics, automated methods of using the electronic health record (EHR) are an attractive option. However, the EHR has often not delivered on its potential.…”
mentioning
confidence: 99%
“…Prior work has raised significant questions about oncologists' communication with patients about the goals of chemotherapy and end-of-life decision making, 33,34 and other work has underscored the potential for devastating financial impact of cancer and its treatment. 35,36 Inadequate communication about the potential physical and financial harms of chemotherapy may contribute to patterns of recommendations consistent with those we observed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…For example, one recent retrospective cohort study of patients with advanced solid tumors diagnosed and followed at Veterans Affairs (VA) hospitals found that study patients only received appropriate nonhospice palliative care 49.5 percent of the time, even within a health delivery system into which palliative care is deeply penetrated and well integrated [30]. Further research clarifying the barriers to appropriate implementation of high-value palliative care in health systems is imperative so that sustainable programs can develop and flourish nationally.…”
Section: Promoting High-value Practices In Palliative Care For Cancermentioning
confidence: 99%